Biological control of Fusarium solani causing wilt of chilli - M.B. PATIL; P.S. PRASAD, G.S. DEVIKA RANI, M.K. NAIK*, (Indian Phytopathology, 2009)
The performance of six Trichoderma and four Pseudomonas isolates were evaluated for their bio control efficacy and ability to induce systemic resistance against Fusarium solani causing wilt of chilli which is posing a serious threat to chilli cultivation in the irrigated tracts of black cotton soil in India. Among six Trichoderma isolates, maximum inhibition was noticed in T. viride (indigenous) followed by T. viride – 16 and T. harzianum – 10. Among four bacterial bio-agents, an indigenous isolate of Pseudomonas fluorescens [Pf- I] was most efficient with 74.26% inhibition followed by P. fluorescens-PGPR isolate. The bio-agents when coated on seeds of popular chilli cultivars, T. viride – 16 and T. viride (indigenous) isolates were best in terms of inhibition with out affecting germination of seeds. In case of bacterial bio-agents, the inhibition was above 68.89% on chilli cultivar Byadagi Kaddi by Pf-I. Efficient bio-agents when treated on seeds, T. viride reduced the propagules of the pathogen from 10.32 X103 cfu g-1 of soil to 1.4 X103 cfu g-1 of soil followed by T. viride- 16. The Pf-I showed highest induction of systemic resistance on chilli plants with increased seed germination and vigour index when challenge inoculated with F. solani.